Combined Effect of Basalt Fibers and Bentonite Clay on Complex Mortar Properties - Karamyan, Hasmik; Avagyan, Mariam; Shainova, Roza; Sahakyan, Anush; Baghdagyulyan, Armine; Tepanosyan, Gevorg; Poghosyan, Zhenya; Aperyan, Araksya; Melikyan, Yeghvard; Badalyan , Maria (Civil Engineering Journal, 2025)
This study examined the effects of basalt microfibers and amorphous-structured bentonite clay on the properties of complex mortar mixtures composed of cement and quicklime, utilizing locally sourced raw materials. Bentonite clay was subjected to thermal treatments at 400, 600, and 1000°C, and a technogenic pozzolanic additive was incorporated to investigate its influence on mortar performance. Optimal results were observed for the clay treated at 600°C, which was subsequently used in the mortar formulations. The primary objective was to assess the effects of varying basalt microfiber dosages (0.5%, 1%, and 2%) and thermally treated bentonite clay concentrations (5%, 15%, and 25%) on the chemical composition, physico-mechanical properties, and structural development of the resulting multi-component systems. Advanced analytical techniques, including SEM/EDS, XRD, FTIR, XRF, DLS, and thermochemical analyses (TG/DTG, TG/DSC, and TG/MS), were used to evaluate the mineralogical composition, particle size distribution, microstructure, and thermal behavior. The findings show that the combined use of basalt microfibers and thermally treated bentonite clay significantly enhanced the mechanical strength and structural formation of the mortars. This study provides novel insights into the synergistic effects of these components, offering a promising approach for enhancing mortar performance using locally sourced materials.